CAMPUR KODE DALAM STATUS PENGGUNA BLACKBERRY MESSENGER - Mutiara, Dona; Faizah, Hasnah; ', Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is titled mixed code in the status of blackberry messenger user. This study aims to find the form of mixed code in the status contained in the blackberry messenger. This research type is qualitative research with descriptive method. The data of this study is to mix meaningful code mix the code out and mix the code into. Data were obtained using reading technique and data validity obtained by documentation technique. Then, the data were analyzed by identifying and classifying based on mixed forms of code. Based on data analysis that has been done, the writer finds mixed code in the form of mixed code outside the mixed code coming from Foreign language or speakers in communicating insert Foreign language into Indonesian, like mix English code. Mix code mixed code into mixed code that comes from the original language by inserting the local language into Indonesian, such as mix Minang language code, Java language, Malay language, Sundanese.Keywords: Mix code, mix code in and out, and blackberry messenger.